The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.26719/2017.23.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hepatitis C viral load and hepatitis C Core antigenaemia among Egyptians

Abstract: Hepatitis C virus (HCV) infection is widespread in Egypt.This study compared HCV RNA with HCVcAg for the detection and quantification of viraemia among a sample of Egyptians. Sera from 80 suspected HCVpositive individuals were tested simultaneously for HCV-RNA load using real-time polymerase chain reaction (PCR) and HCVcAg level using ELISA. Of the 80 samples, 25% were HCV-RNA-negative. HCVcAg was detected in all samples: range 0.4-2462 ng/mL, mean 460 (SD 506) ng/mL. The sensitivity and specificity of HCVcAg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Meanwhile, Ergunay et al [33] revealed 75.8% sensitivity. A group of studies recorded sensitivity of more than 90%, ranging from 93.26 to 96.3% as documented by Kotb et al and Demircili et al [34,35]. Miedouge et al reported that HCVcAg sensitivity was 100% [36].…”
Section: Discussionmentioning
confidence: 92%
“…Meanwhile, Ergunay et al [33] revealed 75.8% sensitivity. A group of studies recorded sensitivity of more than 90%, ranging from 93.26 to 96.3% as documented by Kotb et al and Demircili et al [34,35]. Miedouge et al reported that HCVcAg sensitivity was 100% [36].…”
Section: Discussionmentioning
confidence: 92%
“…Since, the cost of an HCV RNA assay is generally several-fold that of an HCVcAg assay (8,21); therefore, using HCVcAg assays instead of HCV RNA assays might reduce the cost of diagnosis and the time taken to obtain results, and improve patient follow-up in certain environments. In fact, the results of a study that compared an HCV RNA assay with an HCVcAg assay for the detection and quantification of HCV viremia in Egyptian participants led the authors to conclude that while the HCV RNA assay remains the gold standard for the diagnosis of an active HCV infection, an HCVcAg assay can be used when PCR is not available (22).…”
Section: Discussionmentioning
confidence: 99%